2006
DOI: 10.1111/j.1752-7325.2006.tb02572.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Xerostomia in Population‐based Samples: A Systematic Review

Abstract: The consequences of xerostomia on oral health have been studied for decades; however, the actual prevalence of this disorder on the general population remains controversial. The purpose of this systematic review was to determine the prevalence of xerostomia in population-based samples. Electronic databases were screened for relevant articles and reference lists of pertinent articles were also hand-searched. Thirteen articles meeting the final inclusion criteria were identified. Based on the definition of xeros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
123
5
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 61 publications
11
123
5
7
Order By: Relevance
“…In the present study, antihistamines and bronchodilators more than other pharmaceutical groups can cause xerostomia. Orellana (13) and Murray Thomson et al (9) achieved similar results too. Although in our study the influence of bronchodilators on xerostomia was more noticeable, other studies often have pointed that tranquilizers and antidepressants caused xerostomia (7,10,16).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In the present study, antihistamines and bronchodilators more than other pharmaceutical groups can cause xerostomia. Orellana (13) and Murray Thomson et al (9) achieved similar results too. Although in our study the influence of bronchodilators on xerostomia was more noticeable, other studies often have pointed that tranquilizers and antidepressants caused xerostomia (7,10,16).…”
Section: Discussionsupporting
confidence: 73%
“…The prevalence of xerostomia in the studied population was 35.8%. The results of a systematic review determined that the prevalence of dry mouth in 13 selected articles ranged from 0.9% to 64.8% (3,13). Rad et al (2013, Kerman) (3) reported that the prevalence of xerostomia in 1010 Kermanian subjects in Iran was 55%.They evaluated subjective xerostomia while we investigated objective xerostomia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deficiência na secreção salivar, conhecida como xerostomia, é uma queixa muito comum por estar associada às doenças autoimunes, radioterapia e utilização de certos medicamentos. 8,9 Muitas queixas estão associadas a estas alterações fisiológicas que ocorrem no organismo com o passar dos anos, e tais alterações na cavidade bucal, no entanto, podem ser controladas e prevenidas, o que deixa de lado a ideia de que envelhecimento significa contrair doenças bucais. A necessidade de mudança desta imagem negativa foi ressaltada na literatura, e profissionais da área da saúde devem ter cuidados especiais e diferenciados com o paciente idoso.…”
Section: Introductionunclassified
“…10,11 Raquel Pippi ANTONIAZZI (a) Amanda Rodrigues SARI (b) Maísa CASARIN (c) Cristina Machado Bragança de MORAES (a) Carlos Alberto FELDENS (d) Hyposalivation is defined as an objective measure of a reduction in salivary flow and is associated with xerostomia, which is the subjective perception of dry mouth. 12 Hyposalivation can be caused by different factors, such as systemic diseases, the use of medications, radiotherapy of the head and neck, 12 and the use of illicit drugs. 13,14 Cannabis, ecstasy, and methamphetamine are illicit drugs already associated with dry mouth.…”
Section: Introductionmentioning
confidence: 99%